2012
DOI: 10.1021/jp2065503
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Confinement Effect on Electron Transfers Induced by t-Stilbene Sorption in Medium Pore Acidic Zeolites

Abstract: The mere exposure of trans-stilbene (t-St) to three types of dehydrated medium pore acid zeolites that differ by their pore diameter induces t-St spontaneous ionization in high yield. In situ diffuse reflectance UVÀvisible, EPR, and Raman spectra recorded over several months highlight the exceptional stability of the charge separated states formed in ferrierite (H-FER), H-MFI, and mordenite (H-MOR). The increase in the pore diameter from H-FER to H-MOR induces different behaviors after radical cation formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
63
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(82 citation statements)
references
References 71 publications
18
63
1
Order By: Relevance
“…[10][11][12][13][14][15][16][17] In case of high internal electrostatic field and if the confinement is high enough, ionization can occur spontaneously. [18][19][20][21][22][23][24][25] This feature was often observed with sorption of polyaromatics in the channels of medium pore acid zeolites [20][21][22][23][24] or in frameworks containing cations like Li + small enough to generate highly polarizing environment. 26 Thus, the ionizing capacity of the host was shown to depend significantly on the zeolite structure and on the Si/Al ratio but also on the charge balancing cation nature.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…[10][11][12][13][14][15][16][17] In case of high internal electrostatic field and if the confinement is high enough, ionization can occur spontaneously. [18][19][20][21][22][23][24][25] This feature was often observed with sorption of polyaromatics in the channels of medium pore acid zeolites [20][21][22][23][24] or in frameworks containing cations like Li + small enough to generate highly polarizing environment. 26 Thus, the ionizing capacity of the host was shown to depend significantly on the zeolite structure and on the Si/Al ratio but also on the charge balancing cation nature.…”
Section: Introductionmentioning
confidence: 88%
“…To our knowledge, this spectrum does not correspond to any previously reported spectrum for p-QPh related compounds. Based on our own experience in such systems and by analogy with previous works related to electron donor ability of ZSM-5 zeolite framework towards electron deficient radical cations of biphenyl, p-terphenyl, naphthalene, tetracene, and t-stilbene, 21,22,23,24,28,29,39,40,41 this spectrum is tentatively assigned to a charge transfer complex (AlO 4 •+ -p-QPh) associated with the formation of an electronhole pair due to subsequent electron transfer occurring after the radical formation according to equation 3.…”
Section: Eprmentioning
confidence: 99%
“…The spectral features of this long lived charge separated state and its formation mechanism related to the electron donor property of zeolite were detailed in previous papers. [16] The spectra recorded for ten hours, fourteen days and nine months after mixing t-stilbene with H-ZSM-5 zeolites of different Si/Al ratios are shown in Fig. 7.…”
Section: Charge Transfer In Zeolites Of Different Si/al Ratiosmentioning
confidence: 99%
“…The effects of high intrachannel electrostatic field due to aluminium, charge balancing cation and confinement of the guest molecule give rise to intermolecular non-covalent interactions that can induce many interesting reactions. [1,2] Particularly, these remarkable intrinsic properties can include spontaneous ionization, stabilization of otherwise unstable radicals, polymerization and hole-catalyzed reactions. [3][4][5] Indeed, recent studies have demonstrated the determinant role of electron transfer processes in the reaction mechanisms involved in zeolite catalysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation